" ZIYARAH TOURISM " IN BRINGING ITS BRAND TO INTERNATIONAL TOURISM MARKETS INNOVATIVE MARKETING AND ITS IMPORTANCE - Anvar Aidjanovich Khudoyarov (Journals Park Publishing, 2023)
Marketing activity in international tourism markets is manifested as the main mechanism of effective activity of national tourism enterprises and organizations aimed at gaining competitiveness in world markets. Pilgrimage tourism in our country " Ziyarah tourism " in order to develop the developed work of integrated marketing concept in creating a competitive national tourist product based on the brand and bringing it to the world tourism services market serves the development of the field.